2005
DOI: 10.1007/s00421-005-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Iron-regulatory protein hepcidin is increased in female athletes after a marathon

Abstract: The propose of this study was to determine the influence of marathon race on hepcidin excretion in female athletes (age 26-45 years). Urine samples were taken before, immediately after, 1 and 3 days after the race. In the average, hepcidin transiently increased at day 1 from 32 to 85 ng/mg creatinine. We propose that the frequently observed iron deficiency of females runners is caused by elevated hepcidin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
113
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 14 publications
11
113
3
1
Order By: Relevance
“…Such an outcome would suggest that 12 h of recovery provides a sufficient amount of time for an athlete to restore their hepcidin activity to resting levels when conducting the type of running training outlined here, since the hepcidin response showed a significant decline in the 12-h post-T2 LSD . This outcome contrasts that of Roecker et al (2005), who found significantly elevated hepcidin levels 24 h after the completion of exercise. This difference may be explained by the duration and intensity of exercise completed, since the participants of Roecker and colleagues ran four times the distance covered during the T2 LSD run, at an average speed that was 26% slower, and for a duration averaging 3 h 44 min longer.…”
Section: Hepcidincontrasting
confidence: 79%
See 2 more Smart Citations
“…Such an outcome would suggest that 12 h of recovery provides a sufficient amount of time for an athlete to restore their hepcidin activity to resting levels when conducting the type of running training outlined here, since the hepcidin response showed a significant decline in the 12-h post-T2 LSD . This outcome contrasts that of Roecker et al (2005), who found significantly elevated hepcidin levels 24 h after the completion of exercise. This difference may be explained by the duration and intensity of exercise completed, since the participants of Roecker and colleagues ran four times the distance covered during the T2 LSD run, at an average speed that was 26% slower, and for a duration averaging 3 h 44 min longer.…”
Section: Hepcidincontrasting
confidence: 79%
“…However, the levels of the iron-regulatory hormone hepcidin are also increased after exercise (Roecker et al 2005;Peeling et al 2008b). Hepcidin is a liver-produced peptide hormone, up-regulated in response to elevated iron levels and the inflammatory cytokine interleukin-6 (IL-6) (Kemna et al 2005a;Nemeth et al 2004a, b).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies (14)(15)(16) confirmed a role for hepcidin in regulating iron absorption and suggested that the high prevalence of iron deficiency reported in obese adults (17) may be affected by inflammation-mediated hepcidin release (18). In addition, several studies (19)(20)(21) have shown transient increases in urinary hepcidin concentrations and inflammation after exercise. These studies suggested that high levels of physical training, such as military training, may compromise iron homeostasis.…”
Section: Introductionmentioning
confidence: 94%
“…Blood hepcidin concentration is known to determine the amount of plasma iron availability for the body, by controlling iron export from macrophages and enterocytes. To our knowledge, the only types of exercise which have been explored for hepcidin variations are the marathon race (more than 4 h) of female athletes and the 10-km run of male athletes (70-90% VO 2 ) where hepcidin concentration increased despite marked interindividual variations (Peeling et al 2009;Roecker et al 2005).…”
Section: Introductionmentioning
confidence: 99%